Influence of Pheromone-Baited Traps on Stink Bugs in Cotton. Issue 1 (19th February 2019) - Tillman, P Glynn; Cottrell, Ted E
Abstract: Stink bugs (Hemiptera: Pentatomidae) are economic pests in fruit, vegetable, grain, and row crops worldwide. Pyramid traps baited with lures of stink bug aggregation pheromones capture these pests in the field, but stink bugs can congregate on plants near traps. Our specific objective was to examine the area of arrestment of stink bugs based on their density on cotton at different distances from pheromone-baited traps. We used lures of the aggregation pheromone of Euschistus spp., methyl (2 E, 4 Z )-2, 4-decadienoate (MDD), and Plautia stali Scott, methyl [2 E, 4 E, 6 Z ]-2, 4, 6-decatrienoate (MDT). Overall, Euschistus servus (Say), Euschistus tristigmus (Say), Chinavia hilaris (Say), and Nezara viridula (L.) were the main stink bug species on cotton. Over the 3-yr study, adult stink bug density was significantly higher on the row of cotton immediately adjacent to a pheromone-baited trap than on the second and third row from the trap. Stink bug density was significantly lower on the seventh cotton row beyond the trap in 2015, on the fourth, eighth, and 16th rows in 2017, and on the fourth and eighth rows in 2018 compared to the two or three rows nearest the trap. These results indicate that adult stink bugs congregated mainly on the three cotton rows (2.73 m in width) nearest a trap. Management strategies utilizing pheromone-baited traps for stink bug control, such as trap cropping in combination with traps, should take into consideration this area of arrestment.